One pot four component reaction of isocyanides, dimethyl acetylenedicarboxylate and cyclobutene-1,2-diones: synthesis of spiro heterocycles - Nair, Vijay; Menon, Rajeev S.; Deepthi, Ani B.; Devi, Rema; Biju, Akkattu T. (Tetrahedron Letters, 2005)
Isocyanides, dimethyl acetylenedicarboxylate, and cyclobutene-1,2-diones react in one-pot to afford novel spirocyclic compounds with double insertion of the isocyanide.

Reaction of diaryl-1,2-diones with triphenylphosphine and diethyl azodicarboxylate leading to N, N-dicarboethoxy monohydrazones via a novel rearrangement - Nair, Vijay; Biju, Akkattu T.; Abhilash, K. G.; Menon, Rajeev S.; Eringathodi, Suresh (Organic Letters, 2005)
A mechanistically novel reaction of diaryl-1,2-diones with diethyl azodicarboxylate and triphenylphosphine to afford N,N-dicarboethoxy monohydrazones is described. The reaction proceeds via a nitrogen to nitrogen migration of a carboethoxy group.

Engaging zwitterions in carbon-carbon and carbon-nitrogen bond- forming reactions: a promising synthetic strategy - Nair, Vijay; Menon, Rajeev S.; Sreekanth, A. R.; Abhilash, N.; Biju, Akkattu T. (Accounts of Chemical Research, 2006)
An Account of carbon−carbon and carbon−nitrogen bond-forming reactions mediated by zwitterions generated by the addition of organic nucleophiles to activated unsaturated systems highlighting their synthetic potential is presented.

Employing homoenolates generated by NHC catalysis in carbon-carbon bond-forming reactions: state of the art - Nair, Vijay; Menon, Rajeev S.; Biju, Akkattu T.; Sinu, C. R.; Paul, Rony Rajan; Jose, Anu; Sreekumar, Vellalath (Chemical Society Reviews, 2011)
Homoenolate is a reactive intermediate that possesses an anionic or nucleophilic carbon beta to a carbonyl group or its synthetic equivalent. The recent discovery that homoenolates can be generated from alpha,beta-unsaturated aldehydes via N-Heterocyclic Carbene (NHC) catalysis has led to the development of a number of new reactions. A majority of such reactions include the use of carbon-based electrophiles, such as aldehydes, imines, enones, dienones etc. resulting in the formation of a variety of annulated as well as acyclic products. The easy availability of chiral NHCs has allowed the development of very efficient enantioselective variants of these reactions also. The tolerance showed by NHCs towards magnesium and titanium based Lewis acids has been exploited in the invention of cooperative catalytic processes. This tutorial review focuses on these and other types of homoenolate reactions reported recently, and in the process, updates the previous account published in 2008 in this journal.

1,2-Benzoquinones in Diels-Alder reactions, dipolar cycloadditions, nucleophilic additions, multicomponent reactions and more - Nair, Vijay; Menon, Rajeev S.; Biju, Akkattu T.; Abhilash, K. G. (Chemical Society Reviews, 2012)
A brief account of the recent developments in the chemistry of 1,2-benzoquinones is presented in this tutorial review. The title compounds exhibit commendable versatility in both Diels-Alder and dipolar cycloaddition reactions. They have also been employed as electrophilic reaction partners in nucleophile-triggered catalytic processes and related multicomponent reactions. These, along with other reactions described here, lead to the synthesis of densely functionalised carbocyclic and heterocyclic frameworks that are otherwise difficult to access.

Recent advances in employing homoenolates generated by N-heterocyclic carbene (NHC) catalysis in carbon-carbon bond-forming reactions - Menon, Rajeev S.; Biju, Akkattu T.; Nair, Vijay (Chemical Society Reviews, 2015)
The use of NHCs for generating homoenolate species has gained widespread popularity in recent years. A number of highly stereoselective processes of NHC-homoenolates have emerged. Homoenolate reactions have also been employed as key steps in the total synthesis of a number of natural products. The use of compatible co-catalysts, improved NHC-catalyst design and the use of novel precursors for homoenolate generation are among the major developments in this area that were disclosed recently. This tutorial review organises and presents the advancements in this rapidly growing area of catalysis and in the process updates a previous account published in 2011 in this journal.

Recent advances in N-heterocyclic carbene (NHC)-catalysed benzoin reactions (vol 12, pg 444, 2016) - Menon, Rajeev S.; Biju, Akkattu T.; Nair, Vijay (Beilstein Journal of Organic Chemistry, 2016)
Keywords: acyloin reaction; benzoin reaction; N-heterocyclic carbenes; organocatalysis; umpolung

Recent advances in N-heterocyclic carbene (NHC)-catalysed benzoin reactions - Menon, Rajeev S.; Biju, Akkattu T.; Nair, Vijay (Beilstein Journal of Organic Chemistry, 2016)
N-Heterocyclic carbenes (NHCs) have emerged as a powerful class of organocatalysts that mediate a variety of organic transformations. The Benzoin reaction constitutes one of the earliest known carbon-carbon bond-forming reactions catalysed by NHCs. The rapid growth of NHC catalysis in general has resulted in the development of a variety of benzoin and benzoin-type reactions. An overview of such NHC-catalysed benzoin reactions is presented.
Keywords: acyloin reaction; benzoin reaction; N-heterocyclic carbenes; organocatalysis; umpolung